2022
DOI: 10.3389/fcimb.2022.975398
|View full text |Cite
|
Sign up to set email alerts
|

Serological cross-reactivity among common flaviviruses

Abstract: The Flavivirus genus is made up of viruses that are either mosquito-borne or tick-borne and other viruses transmitted by unknown vectors. Flaviviruses present a significant threat to global health and infect up to 400 million of people annually. As the climate continues to change throughout the world, these viruses have become prominent infections, with increasing number of infections being detected beyond tropical borders. These include dengue virus (DENV), West Nile virus (WNV), Japanese encephalitis virus (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 136 publications
0
27
0
Order By: Relevance
“…These viruses are not endemic in Europe and are considered to be travelrelated. While we did not review our participants' vaccination status against YFV and JEV, it is known that these viruses induce of cross-reactive antibodies against TBEV [25]. The rate of other flavivirus vaccinations and/or infections may be higher than observed in this study as the primary inclusion criterion was the presence of TBEV IgG antibodies.…”
Section: Discussionmentioning
confidence: 91%
“…These viruses are not endemic in Europe and are considered to be travelrelated. While we did not review our participants' vaccination status against YFV and JEV, it is known that these viruses induce of cross-reactive antibodies against TBEV [25]. The rate of other flavivirus vaccinations and/or infections may be higher than observed in this study as the primary inclusion criterion was the presence of TBEV IgG antibodies.…”
Section: Discussionmentioning
confidence: 91%
“…Flavivirus including Zika virus (ZIKV), West Nile virus (WNV), Chikungunya virus (CHIKV), Wesselsbron, Talaguine and Sindbis viruses were serologically identified in human populations and in wild animals in Southern and Western Ethiopia [38]. Despite potential serological cross-reactivity due to the broad antigenic cross-reactivity of antibodies and clinical presentation similarities with causing febrile illness to these Flavivirus infections [39], DENV infection was not identified and reported until the last decade in Ethiopia.…”
Section: Denv Infection In Ethiopiamentioning
confidence: 99%
“…The PRNT plays an important role in confirming ZIKV infections, as well as in identifying false-positive ZIKV IgM results to rule out ZIKV infection. Previous studies have shown serologic cross-reactivity between ZIKV and related flaviviruses, including DENV, but the degree to which neutralizing antibody cross-reactivity limits the ability to identify the specific virus responsible for the current infection is not clear (29). One published report suggests that relative levels of neutralizing antibody titers can distinguish ZIKV from DENV infections, especially in specimens collected months after infection (30).…”
Section: Discussionmentioning
confidence: 99%